Strategi Ibu Tunggal (Single Mother) dalam Membentuk Regulasi Diri Remaja - Agustin Mega Purnamawati; Ahmad Fauzi (Institut Agama Islam Negeri Curup, 2023)
This research is motivated by the phenomenon of the success of single mothers in shaping the self-regulation of adolescent children in Tulungagung. Status as a single mother demands to be able to carry out his dual role as a substitute for the ideal father's role as the main breadwinner in the family. In living life and achieving success in life, one needs to have self-regulation since childhood. In the process of forming self-regulation, parents, especially single mothers, have a very large role and influence. This study was conducted to find out how the strategies used by single mothers in forming self-regulation in adolescents in Tulungagung, and to find out how the picture of self-regulation possessed by adolescents from the implementation of the strategies carried out. This study uses a qualitative method with a phenomenological approach. The focus of this research is on a person's subjective experiences and interpretations of the world. Data collection techniques in this study through interviews, observation and documentation. Sampling technique in this study using purposive sampling technique. The results of this study are the first there are several strategies carried out by single mothers in forming self-regulation of adolescent children, namely by providing advice and support, controlling and supervising, instilling an attitude of responsibility and independence. The second is a picture of adolescent self-regulation from the implementation of the strategy, namely the existence of clear and directed planning for the future in achieving the goals of a teenager.